2020
DOI: 10.1128/mbio.02939-20
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vpr-Induced Proinflammatory Response and Apoptosis Are Mediated through the Sur1-Trpm4 Channel in Astrocytes

Abstract: Successful treatment of HIV-infected patients with combinational antiretroviral therapies (cART) can now prolong patients’ lives to nearly normal life spans. However, the new challenge faced by many of those HIV-infected patients is chronic neuroinflammation and neurotoxicity that often leads to HIV-associated neurocognitive disorders (HAND). However, the mechanism of neuropathogenesis underlying HAND, especially in those who are under cART, is not well understood. HAND is typically characterized by HIV-mediat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…Inhibition of NF-κB activity can reverse neuronal autophagy induced by Tat 91 . We recently reported that HIV-1 Vpr-induced proinflammatory response and apoptotic cell death are mediated through the NF-kB activation in astrocytes 92 . Targeting NFkB may ameliorate HIV-associated neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of NF-κB activity can reverse neuronal autophagy induced by Tat 91 . We recently reported that HIV-1 Vpr-induced proinflammatory response and apoptotic cell death are mediated through the NF-kB activation in astrocytes 92 . Targeting NFkB may ameliorate HIV-associated neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-associated neurocognitive disorders (HAND) are characterized by glial activation, cytokine/chemokine dysregulation, and neuronal damage, thought to be a result of chronic neuroinflammation and neurotoxicity [ 201 ]. It has been speculated that HIV-1 viral protein R (Vpr), may contribute to HAND.…”
Section: Sur1-trpm4 Expression and Inhibition In Other Neurological Conditionsmentioning
confidence: 99%
“…It has been speculated that HIV-1 viral protein R (Vpr), may contribute to HAND. A recently published single study has evaluated the role of SUR1-TRPM4 expression patterns and inhibition in a preclinical mouse models of HIV (Tg26) as well as postmortem human tissue [ 201 ].…”
Section: Sur1-trpm4 Expression and Inhibition In Other Neurological Conditionsmentioning
confidence: 99%
See 2 more Smart Citations